1997
DOI: 10.1016/s0895-7061(97)00275-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of PTH(1-34) on Blood Pressure, Renal Function, and Hormones in Essential Hypertension The Altered Pattern of Reactivity May Counteract Raised Blood Pressure

Abstract: As it has been suggested that parathyroid hormone (PTH) is implicated in the pathophysiology of essential hypertension, the effects of PTH(1-34) were assessed during infusion over 120 min in ten men with essential hypertension and in ten healthy men. Ionized calcium was kept constant by a clamping technique. Mean arterial blood pressure fell slightly in the patients (116 mm Hg, median, before, and 108 mm Hg during the infusion, P < .01), but remained unchanged in the controls (median 87 mm Hg). The pulse rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
3

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 54 publications
0
34
0
3
Order By: Relevance
“…Thus, Hulter et al (35) found that a 12-day chronic PTH infusion in normal subjects caused hypertension, an effect however, that could also be the result of the accompanying hypercalcaemia. On the other hand, in the elegant study by Jespersen et al (36), serum ionised calcium level was kept constant by a clamping technique, and a 120-min infusion with PTH caused a reduction in mean arterial blood pressure in hypertensive men. This obviously needs further study, and could possibly have therapeutic implications.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Hulter et al (35) found that a 12-day chronic PTH infusion in normal subjects caused hypertension, an effect however, that could also be the result of the accompanying hypercalcaemia. On the other hand, in the elegant study by Jespersen et al (36), serum ionised calcium level was kept constant by a clamping technique, and a 120-min infusion with PTH caused a reduction in mean arterial blood pressure in hypertensive men. This obviously needs further study, and could possibly have therapeutic implications.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis was proven by a study showing that intradialytic hypotension was significantly improved after PTX in maintenance hemodialysis patients with secondary HPT [15], in agreement with our findings of the successful correction of hypercalcemia after PTX. In animal and human studies, acute exposure of PTH seemed to reduce BP as a result of the vasodilatory effect [16,17], whereas chronic exposure could induce hypertension through inducing the accumulation of calcium in vascular smooth muscle cells [16,18]. However, we failed to demonstrate the correlation between the reduction of serum calcium or iPTH level and the change of the SBP, DBP and PP after PTX.…”
Section: Discussionmentioning
confidence: 66%
“…In the systemic arterial hypertension, the low levels of calcium ions in the serum, mainly due to the hypercalciuria, can stimulate the compensatory increase in the production of PTH, the main hormone related to the control of the plasmatic level of calcium in the organism. In this way, high levels of PTH tend to contribute to the process of bone remodeling, as they stimulate the osteoclastic activity and mobilize the calcium in the skeleton, and could lead to the decrease of the bone mineral density 20 .…”
Section: Discussionmentioning
confidence: 99%